Aplikasi Pemilihan Supplier Menggunakan Metode Profile Matching (Studi Kasus: Toko Maju Jaya) - Ermis, Iklima; Oktariza, Elsa (POLITEKNIK NEGERI JAKARTA, 2019)
The supplier is a business run by parties who disburse a product to a person or a company. In carrying out its operational activities Maju Jaya Store get supply of products from various suppliers. There are several suppliers selling the same item with different offerings, making it difficult for the shop owner to decide on the supplier to be selected when going to the rest of the goods. Currently supplier selection is done by contacting one by one supplier via telephone to find the best offer. This certainly takes a lot of time as well as cost. Resolving the problems that have been exposed is with the construction of Decision Support System of supplier selection using Profile Matching Method. The supplier selection process begins with the determination of criteria and sub criteria, weighting criteria then calculating and grouping core and secondary factors, calculating the total value, and then the system will display the rank of the supplier to be selected for consideration in decision making. Based on the test that is done alpha and beta testing yield percentage of success equal to 100%. While the real data comparison test and using Profile Matching Method has a success percentage 80%.